Self-Efficacy as a Mediator Between Academic Social Support on Student Engagement in Public High School Students in East Lombok District - Muhammad Andika Tanthawi; Kartika Nur Fathiyah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study originated from the observation of low student engagement among public high school students. Self-efficacy and academic social support are considered key factors that contribute to fostering good student engagement. Therefore, this research aims to investigate the role of self-efficacy as a mediator between academic social support and student engagement among high school students. This quantitative study employed a survey method and was conducted in four public high schools, with a total sample of 377 students. The sampling technique used was purposive sampling. Data collection was carried out using the Student Engagement Scale, the Perceived Academic Support Questionnaire (PASQ), and the Generalized Self-Efficacy Scale (GSES). Validity was assessed through expert judgment, while reliability was tested using Cronbach’s Alpha, yielding. This study examined the relationship between academic social support, self-efficacy, and student engagement at SMA Negeri Lombok Timur. Results showed that self-efficacy mediated the relationship between academic social support and student engagement (significant path c'), suggesting the importance of self-efficacy development in improving student engagement. Keywords: social academic support, student engagement, mediation model